Piloting an online telecoaching community-based exercise intervention with adults living with HIV: protocol for a mixed-methods implementation science study. Issue 3 (30th March 2023) - O'Brien, Kelly K; Ibáñez-Carrasco, Francisco; Carusone, Soo Chan; Bayoumi, Ahmed M; Tang, Ada; McDuff, Kiera; Jiancaro, Tizneem; Da Silva, George; Torres, Brittany; Loutfy, Mona R; Islam, Shaz; Lindsay, Joanne; et al.
Abstract : Introduction: Our aim is to evaluate the implementation of an online telecoaching community-based exercise (CBE) intervention with the goal of reducing disability and enhancing physical activity and health among adults living with HIV. Methods and analysis: We will conduct a prospective longitudinal mixed-methods two-phased intervention study to pilot the implementation of an online CBE intervention with 30 adults (≥18 years) living with HIV who consider themselves safe to participate in exercise. In the intervention phase (0–6 months), participants will take part in an online CBE intervention involving thrice weekly exercise (aerobic, resistance, balance and flexibility), with supervised biweekly personal training sessions with a fitness instructor, YMCA membership providing access to online exercise classes, wireless physical activity monitor to track physical activity and monthly online educational sessions on topics related to HIV, physical activity and health. In the follow-up phase (6–12 months), participants will be encouraged to continue independent exercise thrice weekly. Quantitative assessment: Bimonthly, we will assess cardiopulmonary fitness, strength, weight, body composition and flexibility, followed by administering self-reported questionnaires to assess disability, contextual factor outcomes (mastery, engagement in care, stigma, social support), implementation factors (cost, feasibility, technology), health status and self-reported physical activity. We will conduct a segmented regression analyses to describe the change in level and trend between the intervention and follow-up phases. Qualitative assessment: We will conduct online interviews with a subsample of 10 participants and 5 CBE stakeholders at baseline (month 0), postintervention (month 6) and end of follow-up (month 12) to explore experiences, impact and implementation factors for online CBE. Interviews will be audiorecorded and analysed using content analytical techniques. Ethics and dissemination: Protocol approved by the University of Toronto Research Ethics Board (Protocol # 40410). Knowledge translation will occur in the form of presentations and publications in open-access peer-reviewed journals. Trial registration number: NCT05006391 .